Helicobacter pylori infection reduces disease severity in an experimental model of multiple sclerosis - Cook, Katherine W.; Crooks, James; Hussain, Khiyam; O’Brien, Kate; Braitch, Manjit; Kareem, Huner; Constantinescu, Cris S.; Robinson, Karen; Gran, Bruno (Frontiers in Microbiology, 2015)
Recent research has demonstrated that infection with the bacterial pathogen Helicobacter pylori is less common amongst patients with multiple sclerosis (MS), an inflammatory demyelinating disease of the central nervous system (CNS). We compared the prevalence of H. pylori amongst MS patients and healthy controls, and also investigated the impact of this infection on an animal model for MS, experimental autoimmune encephalomyelitis (EAE). The H. pylori status of 71 MS patients and 42 healthy controls was determined by serology. Groups of C57BL/6 mice were infected with H. pylori, or given a placebo, prior to inducing EAE. Clinical scores were assessed for all mice, and spleens and spinal cord tissue were harvested. CD4+ T cell subsets were quantified by flow cytometry, and T cell proliferation assays were performed. In MS patients the seroprevalence of H. pylori was half that of healthy controls (p=0.018). Over three independent experiments, prior H. pylori infection had a moderate effect in reducing the severity of EAE (p = 0.012). In line with this, the antigen-specific T cell proliferative responses of infected animals were significantly reduced (p=0.001), and there was a 4-fold reduction in the number of CD4+ cells in the CNS. CD4+ populations in both the CNS and the spleens of infected mice also contained greatly reduced proportions of IFNγ+, IL-17+, T-bet+, and RORγt+ cells, but the proportions of Foxp3+ cells were equivalent. There were no differences in the frequency of splenic CD4+cells expressing markers of apoptosis between infected and uninfected animals. H. pylori was less prevalent amongst MS patients. In mice, the infection exerted some protection against EAE, inhibiting both Th1 and Th17 responses. This could not be explained by the presence of increased numbers of Foxp3+ regulatory T cells, or T cell apoptosis. This is the first direct experimental evidence showing that H. pylori may provide protection against inflammatory demyelination in the CNS.